An Unusual Case of a Double Tricuspid and Mitral Valves Infective Endocarditis Complicated by Multiple Septic Embolisms Secondary to an Atrial Septal Defect: A Case Report and Review of Literature - Caterina Monari; Daniele Molinari; Alessandro Cornelli; Loredana Alessio; Francesco Coppolino; Consiglia Barbareschi; Stefania De Pascalis; Michele Torella; Giovanni Cimmino; Marisa De Feo; Nicola Coppola; Tiziana Formisano (Infectious Disease Reports, 2023)
Multivalvular endocarditis (MVE) is an uncommon infection that mostly involves mitral and aortic valves, and it is related to a higher risk of congestive heart failure and a higher mortality. We described a case of a bilateral MVE and performed a review of the literature on similar clinical cases. We reported an unusual case of a 68-year-old male patient with a tricuspid and mitral infective endocarditis due to a methicillin-resistant Staphylococcus aureus complicated by multiple right- and left-sided septic embolization (lungs, brain, spleen, L2–L3 vertebral bones) due to an unknown atrial septal defect identified and repaired during cardiac surgery. Despite the severity of the clinical case, the patient experienced a good clinical outcome also thanks to a multidisciplinary approach. We identified 21 case reports describing bilateral MVE. A multidisciplinary approach is essential in the management of valve diseases to improve the prognosis of patients, especially in bilateral MVE.